Geochemical constraints on Lake Mega-Chad discharge to the Atlantic Ocean during the Holocene - Germain Bayon; Jung-Hyun Kim; Charlotte Skonieczny; Guillaume Soulet; Sujin Kang; Mathilde Levacher; Barnabé Djatibeye; Jean-François Ghienne; Bernard Dennielou; Eduardo Garzanti (Earth and Planetary Science Letters, 2026)

Bidirectional associations between biological aging, cardiovascular health, and cardiovascular risk: findings from the INSPIRE-T lifespan cohort - Mathilde Strumia; Vanina Bongard; Samuel Thuriot; Philippe Cestac; Brigitte Sallerin; Jean-Marc Lemaitre; David Furman; Sophie Guyonnet; Bruno Vellas; Sandrine Andrieu; Laure Rouch; Sophie Guyonnet; et al. (GeroScience, 2026)
Chronological age is a common and non-modifiable factor for chronic disease, but does not fully explain age-related changes. Biological clocks have been developed to explore biological aging mechanisms. They could help identify protective factors against accelerated aging and associated diseases. We aim to assess the association between reduced epigenetic or inflammatory aging and ideal cardiovascular health or cardiovascular risk. We conducted a cross-sectional analysis of participants from the INSPIRE-T cohort. Cardiovascular health (CVH) was assessed using the Life’s Essential 8 score. Cardiovascular risk was assessed using the American Framingham risk score (FRS) and the European Systematic Coronary Risk Evaluation (SCORE2) score. Epigenetic and inflammatory aging was calculated from the residuals from linear regression of biological age (based on five epigenetic clocks and one inflammatory clock) and chronological age. Linear and logistic regression models were used. Better CVH has been associated with slower epigenetic aging, particularly in younger subjects and men. Accelerated epigenetic aging measured by GrimAge was associated with an increase cardiovascular risk (for SCORE2: OR = 1.10 95%CI [1.04; 1.16]). No persistent association was found with the inflammatory clock. Our study reported an association between ideal global CVH with reduced epigenetic aging after adjustment for chronological age and gender. This suggests that epigenetic aging may be modifiable through healthy lifestyle and cardiovascular risk management, although a potential underlying causal relationship remains to be established. Moreover, accelerated epigenetic aging is linked to worsening cardiovascular risk, and could be a new risk factor alongside chronological age. Graphical Abstract

The responsibility of Western European coastal states for the conservation of two emblematic migratory seabirds in the context of offshore wind farms - Alice Bernard; Nicolas Courbin; Jérémy Tornos; Tristan J.B. Martin; Mathilde Lejeune; Aurélien Prudor; Pascal Provost; Adrien Lambrechts; Chris P. Gaskin; Jérôme Cabelguen; Matthieu Bécot; Frédéric Jiguet; et al. (Biological Conservation, 2026)

No impact of black-eye symptom on foraging behaviour and reproductive success of Northern gannets following highly pathogenic avian influenza - Aurore Ponchon; Pascal Provost; Alice Bernard; Thierry Boulinier; Mathilde Lejeune; Amélie Lescroël; Jérémy Tornos; David Grémillet (Biological Conservation, 2026)

Corrigendum to “Mindful eating is associated with a better diet quality in the NutriNet-Santé study” [Appetite 206 (2025) 107797] - Pauline Paolassini-Guesnier; Marion Van Beekum; Emmanuelle Kesse-Guyot; Julia Baudry; Bernard Srour; Alice Bellicha; Rebecca Shankland; Angélique Rodhain; Christophe Leys; Serge Hercberg; Mathilde Touvier; Benjamin Allès; et al. (Appetite, 2025)

Mindful eating is associated with a better diet quality in the NutriNet-Santé study - Pauline Paolassini-Guesnier; Marion Van Beekum; Emmanuelle Kesse-Guyot; Julia Baudry; Bernard Srour; Alice Bellicha; Rebecca Shankland; Angélique Rodhain; Christophe Leys; Serge Hercberg; Mathilde Touvier; Benjamin Allès; et al. (Appetite, 2025)

The Association Between Ultra-Processed Food Consumption and Chronic Insomnia in the NutriNet-Santé Study - Pauline Duquenne; Julia Capperella; Léopold K. Fezeu; Bernard Srour; Giada Benasi; Serge Hercberg; Mathilde Touvier; Valentina A. Andreeva; Marie-Pierre St-Onge (Journal of the Academy of Nutrition and Dietetics, 2024)

The monodominant species Spirotropis longifolia is mainly nodulated by strains of the genus Bradyrhizobium outside the B. japonicum and B. elkanii superclades - Christine Le Roux; Emile Fonty; Laurent Brottier; Mathilde Bernard; Yves Prin; Daniel Sabatier (Symbiosis, 2024)

Rebuttal to the (pre-proof) paper published by S. Peters and H. Verhagen - Mathilde Touvier; Pilar Galan; Chantal Julia; Mélanie Deschasaux-Tanguy; Bernard Srour; Emmanuelle Kesse-Guyot; Valentina A. Andreeva; Serge Hercberg (PharmaNutrition, 2024)

Hyaluronic acid-antigens conjugates trigger potent immune response in both prophylactic and therapeutic immunization in a melanoma model - Alessio Malfanti; Mathilde Bausart; Kevin Vanvarenberg; Bernard Ucakar; Véronique Préat (Drug Delivery and Translational Research, 2023)

Cold-water immersion and whole-body cryotherapy attenuate muscle soreness during 3 days of match-like tennis protocol - Mathilde Poignard; Gaël Guilhem; Marc Jubeau; Erwan Martin; Thibaut Giol; Bernard Montalvan; François Bieuzen (European Journal of Applied Physiology, 2023)

Biomarkers of mitochondrial dysfunction and inflammaging in older adults and blood pressure variability - Leonardo Bencivenga; Mathilde Strumia; Yves Rolland; Laurent Martinez; Philippe Cestac; Sophie Guyonnet; Sandrine Andrieu; Angelo Parini; Alexandre Lucas; Bruno Vellas; Philipe De Souto Barreto; Laure Rouch; et al. (GeroScience, 2023)

Cosmet’eau—Changes in the personal care product consumption practices: from whistle-blowers to impacts on aquatic environments - Adèle Bressy; Catherine Carré; Émilie Caupos; Bernard de Gouvello; José-Frédéric Deroubaix; Jean-Claude Deutsch; Romain Mailler; Anthony Marconi; Pascale Neveu; Laurent Paulic; Sébastien Pichon; Vincent Rocher; et al. (Environmental Science and Pollution Research, 2016)